Exploring the variability of argon loss in Apollo 17 impact melt rock 77135 using high‐spatial resolution 40Ar/39Ar geochronology. (13th January 2019) - Mercer, Cameron M.; Hodges, Kip V.; Jolliff, Bradley L.; Van Soest, Matthijs C.; Wartho, Jo‐Anne; Weirich, John R.
Abstract: 40 Ar/ 39 Ar incremental heating experiments on whole‐rock lunar samples commonly provide evidence of varying degrees of radiogenic 40 Ar ( 40 Ar*) loss. However, these experiments provide limited information about whether or not 40 Ar* is preferentially lost from specific glasses, minerals, or polyphase domains. Ultraviolet laser ablation microprobe (UVLAMP) 40 Ar/ 39 Ar dating and electron probe microanalysis of mineral clasts and polyphase melt assemblages in Apollo 17 poikilitic impact melt rock 77135 show evidence of geochemical controls on 40 Ar/ 39 Ar dates. Potassium‐rich glass and K‐feldspar in the mesostasis are the dominant sources for Ar released during low‐temperature steps of published 40 Ar/ 39 Ar release spectra for this rock, while pyroxene oikocrysts with enclosed plagioclase chadacrysts contribute Ar predominantly to intermediate‐ to high‐temperature steps. Additionally, UVLAMP analysis of a mm‐scale plagioclase clast demonstrates the potential to use stranded 40 Ar* diffusive loss profiles to constrain the thermal evolution of lunar impact melt deposits and indicates that the melt component of 77135 cooled quickly. While some submillimeter clasts of plagioclase are distinctly older than the melt, other small clasts yield dates younger than the oldest melt components in 77135, plausibly due to subgrain fast diffusion pathways and/or 40 Ar* loss during brief episodes of reheating at high temperatures. Our data suggest that integrated petrologic and microanalytical geochronologic studies are necessary complements to bulk sample geochronologic studies in order to fully evaluate competing models for the impactor flux during the first billion years of the Moon's evolution.